1988
DOI: 10.2134/agronj1988.00021962008000040011x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Tillage and Rotation Effects on Corn Growth and Yield on High and Low Organic Matter, Poorly Drained Soils

Abstract: Little information is available that evaluates long-term use of a range of tillage systems and different cropping sequences on poorly drained soils. This study relates corn (Zea mays L.) growth and yield to several reduced tillage systems used with continuous cropping and a corn-soybean (Glycine max L.) rotation. Experiments were conducted on Chalmers silty clay loam (fine-silty, mixed, mesic Typic Haplaquoll) with 40 g kg-• organic matter for 12 yr, and Clermont silt loam (fine-silty, mixed, mesic Typic Ochra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
96
3

Year Published

1994
1994
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(116 citation statements)
references
References 8 publications
17
96
3
Order By: Relevance
“…However, Van Doren et al (1976) reported that maize grain yields are insensitive to tillage over a wide range of soil textures, cropping systems, climate conditions and experiment durations as long as equal plant densities and adequate weed control were maintained. The reduction in crop yields on poorly drained soils under conservation agriculture was also reported by Griffith et al (1988). Increased yields on well-drained soils are attributed to more efficient use of water and improved physical properties (Griffith et al 1986).…”
Section: Effect Of Soil Texturementioning
confidence: 84%
See 3 more Smart Citations
“…However, Van Doren et al (1976) reported that maize grain yields are insensitive to tillage over a wide range of soil textures, cropping systems, climate conditions and experiment durations as long as equal plant densities and adequate weed control were maintained. The reduction in crop yields on poorly drained soils under conservation agriculture was also reported by Griffith et al (1988). Increased yields on well-drained soils are attributed to more efficient use of water and improved physical properties (Griffith et al 1986).…”
Section: Effect Of Soil Texturementioning
confidence: 84%
“…The reduction in crop yields on poorly drained soils under conservation agriculture was also reported by Griffith et al (1988). Increased yields on well-drained soils are attributed to more efficient use of water and improved physical properties (Griffith et al 1986). Low yields in poorly drained soils are attributed to allelopathy (Yakle and Cruse 1984) and plant pathogens (Tiarks 1977).…”
Section: Effect Of Soil Texturementioning
confidence: 84%
See 2 more Smart Citations
“…In contrast, data from the other three years of the experiment show significant differences between treatments, with the CT:NT ratio reaching a value close to 2 (4 th year, barley). This different response might be related with different factors such as irregular rain distribution (both within and between years), variability of local conditions of soil preparation, or soil moisture content at the time of seeding (Griffith et al 1988). The number of pores classified was 65890, of which 36304 corresponded to the CT treatment (0.005 < EPD < 7.395 mm, average = 0.3073 mm and STD = 0.2794, Q1 = 0.1518, Q2 = 0.2228, Q3 = 0.3604, skewness = 5.23).…”
Section: Resultsmentioning
confidence: 99%